LITERASI KAWASAN SOSIOLOGI MAHASISWA DALAM MEMPERSIAPKAN KARYA AKHIR PROGRAM STUDI PENDIDIKAN SOSIOLOGI FKIP UNTAN - Rustiyarso, Rustiyarso (Jurnal Kajian Pembelajaran dan Keilmuan, 2017)
AbstractThis study aimed to describe the education of sociology departement literacy used by students of sociology of education in preparing the final work in FKIP Tanjungpura University of. The method used is descriptive method survey form with a qualitative approach. Data collected by the indirect communication. Data collection tool used is a questionnaire and documentation in the form outline and design student research. The population of this study were all students of sociology of education that has been qualified in completing course credits a number of 110-115 credits and be eligible to apply for the title of the research to the academic supervisor. The research proves that students in general education courses sociology "in line" in preparing for the writing of the final work through the proposed outline and the design of the proposed research to the academic supervisor or to the sociology of education courses. In particular: 1) student of the sociology of education before writing her college thesis to perform a wide variety of approaches and work hard to get a variety of literacy suite of social media both print and non-print; 2) student education study program of sociology in doing literacy courses to prepare for the final works in sociology of education courses to experience various obstacles whether they are economic, technical as well as non-economic and non-technical; 3) the strategies used to overcome various obstacles in literacy preparation was writing the end of college students of education and sociology are doing searching brawshing using a web search engine sociology department, namely Google and Yahoo and other web search engines. Keywords: literacy, education of sociology, end of college preparatory works